Literatur Review: Resiliensi Untuk Meningkatkan Kualitas Hidup Pasca Pandemi Covid-19 - Johanna, Petra; Tarigan, Beby Astri; Sitorus, Friyanka H.D; Lumbantoruan, Haposan (Psikologi Prima, 2023)
The purpose of this study is to review that resilience consisting of seven factors, namely emotion regulation, impulse control, optimism, causal analysis, empathy, self-efficacy, and reaching out, is very important to improve the quality of life of post-pandemic Indonesian people, who experienced trauma during the Covid-19 pandemic. This research methodology uses a literature review through analysis of theories from journals and books, articles, and other sources related to the focus of research. The results of this literature research state that humans experiencing physiological and psychological suffering during the Covid-19 pandemic are able to maintain and improve their quality of life, called resilience. Reivich and Shatte (2002) stated resilience is the ability to control pressure, adversity, or trauma by making healthy and productive responses in daily life. When individuals, families, communities and communities and nations have resilient and have a healthy quality of life, then the nation recovers and becomes strong again.